Reassessing Machine-Mediated Fatwā Authority: The Epistemic Limits of the AiDeen Chatbot in Light of Shāfi‘ī Uṣūl al-Fiqh - Nabilah Rohadatul Aisyah (Zamzami Scholar Publishing, 2026)
The expansion of artificial intelligence (AI) as a digital religious assistant, such as AiDeen on the Muslim Pro platform, marks a shift in the landscape of fatwa authority in the digital age and raises epistemological questions regarding its methodological legitimacy. This article aims to evaluate the validity of AiDeen's religious responses within the framework of Shāfi‘ī uṣūl al-fiqh, emphasizing the aspects of mufti qualifications and the procedure of istinbāṭ al-aḥkām. This study uses a descriptive-evaluative qualitative approach, grounded in a literature review and an interactive simulation of ten fiqh issues. The findings show that AiDeen operates at an informative-descriptive level without demonstrating complete fiqh reasoning. Methodologically, weaknesses were identified in the semantic analysis of arguments, inconsistencies in the hierarchy of legal sources, the absence of a valid tarjīḥ mechanism, and the absence of a dimension of reflective awareness and ethical responsibility as prerequisites for fatwa authority. This article contributes to formulating normative parameters for evaluating algorithm-based legal products and affirms the epistemic limits of AI in contemporary Islamic legal discourse, so that legal authority must remain rooted in methodological integrity and the accountability of scholars.